ANALYZING RISK FACTORS AND OUTCOMES OF NEONATAL HEARING SCREENING - DESAI, TRIVENI; MANTHALE, AISHWARAYA; KAMATH, RASHMI; SHIRSHETTY, ARUNKUMAR (International Journal of Current Pharmaceutical Research, 2025)
Objective: Neonatal hearing loss can significantly impact a child's developmental trajectory. This study evaluates the risk factors associated with neonatal hearing impairment and analyzes the outcomes of a hearing screening program at a tertiary care center. Methods: This prospective observational study involved 1175 neonates screened for hearing loss using Otoacoustic Emissions (OAE). Data were collected on high-risk factors such as consanguinity, family history of deafness, ototoxic drug exposure, and low birth weight, and their association with screening outcomes. Results: The prevalence of high-risk factors included consanguinity (13.53%), family history of deafness (0.17%), ototoxic drug intake (0.26%), and low birth weight (19.91%). Of those initially referred for additional testing, 50% were lost to follow-up, and 50% confirmed for further diagnostic evaluation. Associations were noted between consanguinity and referral rates, as well as a strong correlation between family history and referrals. Conclusion: The study highlights the effectiveness of initial neonatal hearing screenings but indicates the need for improved follow-up systems to ensure comprehensive care for all neonates at risk of hearing loss.